2015
DOI: 10.1155/2015/425987
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Future Caribbean Rainfall and Temperature Extremes across Rainfall Zones

Abstract: End-of-century changes in Caribbean climate extremes are derived from the Providing Regional Climate for Impact Studies (PRECIS) regional climate model (RCM) under the A2 and B2 emission scenarios across five rainfall zones. Trends in rainfall, maximum temperature, and minimum temperature extremes from the RCM are validated against meteorological stations over 1979–1989. The model displays greater skill at representing trends in consecutive wet days (CWD) and extreme rainfall (R95P) than consecutive dry days (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 51 publications
2
36
0
Order By: Relevance
“…Climatology plots of modelled and observed temperature and rainfall extremes were created for six Caribbean zones by averaging the climatology of all stations in the zone (Figure 2). The zones are premised on the work of Jury (2009), Stephenson et al (2014) and McLean et al (2015) and span the north Caribbean (Zone 1) through the southeastern Caribbean (Zone 5) and Belize (Zone 6) (see Figure 2). Spatial plots of the difference between modelled and observed annually averaged extreme rainfall indices are also examined to assess the skill of the model for or within a zone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Climatology plots of modelled and observed temperature and rainfall extremes were created for six Caribbean zones by averaging the climatology of all stations in the zone (Figure 2). The zones are premised on the work of Jury (2009), Stephenson et al (2014) and McLean et al (2015) and span the north Caribbean (Zone 1) through the southeastern Caribbean (Zone 5) and Belize (Zone 6) (see Figure 2). Spatial plots of the difference between modelled and observed annually averaged extreme rainfall indices are also examined to assess the skill of the model for or within a zone.…”
Section: Methodsmentioning
confidence: 99%
“…It is useful to note as well that trends in historical temperature (and rainfall) extremes for Caribbean subregions also reflect different responses in magnitude and in some cases direction of the climate change signal. See, for example Stephenson et al (2014) and McLean et al (2015). These provide further justification for exploring the changes spatially and by zones even in relation to temperature.…”
Section: Zonesmentioning
confidence: 97%
“…The main feature of precipitation over the Caribbean is a well-defined annual cycle. Taylor and Alfaro (2005) and Jury (2009c) showed that for most of the region (Belize and the islands of the Caribbean Sea), this cycle is characterized by maximum precipitation from May to November and a dry period peaking in February-March. Particularly in the northwest of the Caribbean, the wet season tends to be bimodal with peaks in May-June (early season) and August-October (late season).…”
Section: Data Sets Usedmentioning
confidence: 99%
“…The basic climatology of the region has been described in a number of earlier works (e.g. the earlier works of Hastenrath previously mentioned) and more recently by Taylor and Alfaro (2005). Many studies (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation